PENGARUH KUALITAS PELAYANAN DAN AKSESBILITAS TERHADAP LOYALITAS PASIEN DI RUANG CEMPAKA RUMAH SAKIT MITRA KELUARGA SURABAYA - jurnalpps pps; Denik Kristanti; Wasis Budiarto; Nugroho Mardi Wibowo (Jurnal Manajerial Bisnis, 2019)
This study tried to analyze the quality of service and accessibility to patient loyalty at the Cempaka Room in Mitra Keluarga Hospital, Surabaya. This study used 50 patients who visited patients at the Cempaka Room in Mitra Keluarga Hospital Surabaya as the study sample. The research method uses quantitative methods. The results showed service quality and simultaneous accessibility to patient loyalty. Service quality and accessibility are significantly significant for patient loyalty.